2021
DOI: 10.1016/j.apmr.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Limitations and Discharge Destination in Patients With COVID-19

Abstract: Objective The objectives of this study were to identify functional limitations in COVID-19 patients admitted to acute care hospitals, to evaluate functional limitations by demographic, medical and encounter characteristics, and to examine functional limitations in relation to discharge destination. Design and Setting This is a cross sectional, retrospective study of adult patients with COVID-19 who were discharged from two different types of hospitals (academic medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 39 publications
3
28
1
1
Order By: Relevance
“…After participation in PR, further care of the patients was possible in the home environment with the support of walking aids, home care, the help of relatives or oxygen supplementation. These results are in contrast to the findings of Roberts et al showing that physical function deficits in COVID-19 patients were associated with an increased odds ratio of discharge to an institution from acute care hospitals [ 7 ]. In Switzerland, patients with severe COVID-19 infection and persistent significant functional deficits were given the option to be transferred to an inpatient rehabilitation program for post-acute treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…After participation in PR, further care of the patients was possible in the home environment with the support of walking aids, home care, the help of relatives or oxygen supplementation. These results are in contrast to the findings of Roberts et al showing that physical function deficits in COVID-19 patients were associated with an increased odds ratio of discharge to an institution from acute care hospitals [ 7 ]. In Switzerland, patients with severe COVID-19 infection and persistent significant functional deficits were given the option to be transferred to an inpatient rehabilitation program for post-acute treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Complications include respiratory failure, non-pulmonary complications such as acute myocardial injury, renal failure or thromboembolic events, septic shock, and multiple organ failure in severe cases. Therefore, a large number of patients with severe COVID-19 suffer from functional physical and partly psychological limitations [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, other factors may be necessary to identify individuals who require additional services in the acute and early post-acute phase. For example, three recent studies have reported significant associations between impairments in physical function and important outcomes like discharge destination 7 , hospital readmission, 8 and mortality 9 in this population. These results are consistent with a small but growing number of reports highlighting prognostic significance of physical function in hospitalized patients, 10 suggesting that routine assessment of physical function in the hospital may help guide the delivery of care, particularly during a pandemic when resources are stretched.…”
mentioning
confidence: 93%
“…West Java has the most, with approximately 1,200 units, while Maluku has the fewest, with only 22 ventilators. The average number of ventilators available in each hospital is approximately 3-4 units, which is considered insufficient to handle the surge in patient volume (Roberts et al, 2021;Vlachos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%